2023
DOI: 10.1007/s40948-023-00541-3
|View full text |Cite
|
Sign up to set email alerts
|

Response and prediction of unsaturated permeability of loess to microstructure

Abstract: The study of water infiltration helps to investigate the pollutants' migration, grasp the mechanism of the water cycle, and correctly evaluate water resources. This paper reveals the mechanism of compacted loess's one-dimensional vertical water infiltration characteristics using a low-cost water infiltration device. In addition, it investigates particle arrangement and pore size distribution characteristics using nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM). The test finding suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This paper considered the effect of air resistance on GA models based on Wang's method. The time calculated by Wang's method is 2223 s when the infiltration depth reaches 0.2 m. However, several studies 35 , 36 have shown that air resistance can reduce the infiltration rate. Therefore, the infiltration time calculated by the method of this paper is 2513 s. This follows the inference logic.…”
Section: Discussionmentioning
confidence: 99%
“…This paper considered the effect of air resistance on GA models based on Wang's method. The time calculated by Wang's method is 2223 s when the infiltration depth reaches 0.2 m. However, several studies 35 , 36 have shown that air resistance can reduce the infiltration rate. Therefore, the infiltration time calculated by the method of this paper is 2513 s. This follows the inference logic.…”
Section: Discussionmentioning
confidence: 99%
“…Risk coupling theory refers to a theoretical framework in the field of risk management that considers the interactions and influences between different risk factors. It emphasizes the potential interconnections and mutual impacts among various risk factors, which may lead to the occurrence of one risk event or exacerbate the occurrence of others, thereby increasing the overall risk level [ 19 21 ]. Several researchers have explored the coupling effects of multiple risk factors in various industries by constructing N-K models, including marine ship accidents and tunnelling construction accidents [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%